Analysis of the Influence of Competency and Workload on Employee Performance with Presenteism as An Intervening Variable in the Distribution Regulation Implementing Unit (UP2D) PT. PLN (Persero) North Sumatera Distribution Main Unit - Yasri, Afif; Syahrizal, Syahrizal (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the influence of competence and workload on employee performance with presenteeism as an intervening variable at the Distribution Management Implementation Unit (UP2D) of PT. PLN (Persero) North Sumatra Distribution Main Unit. Competence and workload are important factors that influence employee performance in achieving organizational goals, while presenteeism, which refers to the physical presence of employees without optimal productivity, can be a barrier to performance. This study uses a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to employees of UP2D PT. PLN (Persero), and analyzed using the path analysis method to measure the direct and indirect relationships between the variables studied. The results of this study are that Workload has a negative and significant effect on Employee Performance with an original sample value of -0.264 and p values 0.006. Workload has a positive and significant effect on Presenteeism with an original value of 0.379 and p values 0.000. Competence has a positive and significant effect on Employee Performance with an original sample value of 0.300 and p values of 0.001. Competence has a negative and significant effect on Presenteeism with an original sample value of -0.579 and p values of 0.000. Presenteeism has a negative and significant effect on Employee Performance with an original sample value of -0.397 and p values of 0.002. Workload has a negative and significant effect on Employee Performance through Presenteeism with an original sample value of -0.151 and p values of 0.004. Competence has a positive and significant effect on Employee Performance through Presenteeism with an original sample value of 0.230 and p values of 0.008.